Structural and optical properties of graphene quantum dots−polyvinyl alcohol composite thin film and its potential in plasmonic sensing of carbaryl - Muhamad Fauzi, Nurul 'Illya; Fen, Yap Wing; Kamal Eddin, Faten Bashar; Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim (Multidisciplinary Digital Publishing Institute, 2022)
In this study, graphene quantum dots (GQDs) and polyvinyl alcohol (PVA) composite was prepared and then coated on the surface of gold thin film via the spin coating technique. Subsequently, Fourier transform infrared spectroscopy (FT-IR), atomic force microscopy (AFM), and ultraviolet-visible spectroscopy (UV–Vis) were adopted to understand the structure, surface morphology, and optical properties of the prepared samples. The FT-IR spectral analysis revealed important bands, such as O–H stretching, C=O stretching, C-H stretching, and O=C=O stretching vibrations. The surface roughness of the GQDs-PVA composite thin film was found to be increased after exposure to carbaryl. On the other hand, the optical absorbance of the GQDs-PVA thin film was obtained and further analysis was conducted, revealing a band gap Eg value of 4.090 eV. The sensing potential of the thin film was analyzed using surface plasmon resonance (SPR) spectroscopy. The findings demonstrated that the developed sensor’s lowest detection limit for carbaryl was 0.001 ppb, which was lower than that previously reported, i.e., 0.007 ppb. Moreover, other sensing performance parameters, such as full width at half maximum, detection accuracy, and signal-to-noise ratio, were also investigated to evaluate the sensor’s efficiency.